Mapping class groups of h-cobordant manifolds - Samuel Muñoz-Echániz (Forum of Mathematics, Sigma)
We prove that the mapping class group is not an h-cobordism invariant of high-dimensional manifolds by exhibiting h-cobordant manifolds whose mapping class groups have different cardinalities. In order to do so, we introduce a moduli space of ‘h-block’ bundles and understand its difference with the moduli space of ordinary block bundles.